Peran Perencanaan Pembelajaran Terhadap Kualitas Pendidik Dalam Kegiatan Belajar Mengajar Di UPT SDN 060909 - Afrida Juliani; Yunizar Ritonga; Anggi Putri Utami; Sindy Adella; Safran Safran (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
This assessment aims to assess the role of learning planning on the quality of educators in teaching and learning activities, the obstacles faced by teachers in carrying out learning planning at UPT SDN 060909. This research uses qualitative methods with a descriptive approach. The research subjects were all homeroom teachers at UPT SDN 060909 Medan Denai. The obstacle faced by teachers is that real teachers cannot guarantee that all students will be interested because there are also students who do not participate, for example when using the conversation method, students become calmer and still do not answer anything. This discussion method is very important to stimulate student activity. However, teachers always evaluate this to continue to improve the quality of educators so that these plans can be used as reference material for further development. From the research results, it was found that learning planning is very important in teaching activities, because learning planning can be a reference for a teacher to carry out learning in the classroom.